Weed control in rubber plantations - Lima, Adelise de Almeida; Pereira, Roberto José de Carvalho (Pesquisa Agropecuaria Brasileira, 1991)
The efficiency of herbicides and their various combinations applied to post-emergence on weed control was tested in juvenile and developed rubber (Hevea spp) plantations in southern Bahia, Brazil. Three experiments (plots) were conducted under field conditions and the testing applications included: simazine-ametrine + paraquat, alachlor + paraquat, simazine + paraquat and diuron + paraquat, all in dosages of 0.3 + 0.2 kg/ha, respectively; oxifluorfen + paraquat (1.5 + 0.2 kg/ha); metholachlor + paraquat + metribuzin (3.0 + 0.2 + 1.0 kg/ha); simazine-ametrine and etidimuron (3.0 kg/ha); diuron-hexazinone (2.0 kg/ha); glifosate (1.5 kg/ha); dalapon (6.0 kg/ha) plus a control where no herbicide was applied. The herbicides that performed best, with 80-90%; of efficiency, relatively to the control, were glifosate, diuron-ametrine + paraquat and oxifluorfen + paraquat.